Perceptions towards Online System of Teaching and Learning Mathematics (Pragyaratna प्रज्ञारत्न, 2024)
This research paper discusses on the online mode of teaching/learning mathematics especially during the period of COVID-19. The main objective of the study was to analyze the perceptions of students’ and teachers’ towards online system of teaching/learning mathematics. The study was carried out using case study. Four students studying mathematics at B. Ed. level and two teachers teaching at the same level were the participants of this study. Findings of the study showed that online class was less Interactive and there were complications due to Poor Connections. On the other hand, Flexible Learning and Opportunity to Learn in Self Pacing were found to be positive aspects of the system. At the same time, the research concluded two major challenges: challenge of Immediate Feedback and challenge Monitoring Students’ Activities during the class.